A Shared Space - Griffith, James S. (Utah State University, University Libraries, 1995)
Where it divides Arizona and Sonora, the international boundary between Mexico and the United States is both a political reality, literally expressed by a fence, and, to a considerable degree, a cultural illusion. Mexican, Anglo, and Native American cultures straddle the fence; people of various ethnic backgrounds move back and forth across the artificial divide, despite increasing obstacles to free movement. On either side is found a complex cultural mix of ethnic, religious, and occupational groups. In A Shared Space James Griffith examines many of the distinctive folk expressions of this varied cultural region.